Estimated Population Abundance of a Bat (Chiroptera) Colony at the Batukoq Water Channel Cave, Senaru, North Lombok - Rahman, Fatuh; Adiansyah, Joni Safaat; Sukuryadi, Sukuryadi; Akbar, Ilham M (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2025)
Cave-roosting bats are highly exposed to disturbance because roost entrances are predictable and accessible, yet local management often lacks baseline population information. This study examines a cave-associated roost system in Batukoq, Senaru (North Lombok) and aims to provide a site-specific colony abundance estimate, describe emergence dynamics during the counting window, and identify the main sources of counting bias under field conditions relevant to low-resource monitoring. A Flight Line Census based on direct visual observation was implemented without thermal sensors or night-vision devices, conducted during critical movement periods (dusk and dawn) and restricted to a single large colony site to minimize cross-site variability. The colony’s mean estimated abundance was approximately ±590 individuals per night, indicating that Batukoq functions as a key day roost. Visual observations suggested two major groups (Megachiroptera and Microchiroptera) using different flight corridors, and emergence was brief (about 30–45 minutes) with an early peak period that is most sensitive to counting error. The dominant limitation was flight-path overlap under high density and low light, which tends to produce underestimation; therefore, abundance values should be treated as conservative and supported by repeated counts across multiple nights and time windows. These results support the continued use of visual flight-line counts as a non-invasive baseline method, provided that procedural standardization is emphasized and roost disturbance is reduced as a practical conservation priority.